Strategi Manajemen Penguatan Karakter Muslim Khairu Ummah: Peran Majelis Ulama Indonesia (MUI) di Masyarakat Lampung - Amiruddin, Amiruddin; romlah, romlah (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Indonesian Ulema Council, as one of the religious organizations in Indonesia, always proclaims Islam rahmatan lil alamin. This article aims to examine and dig deeper into the principles of khairu umah which are strengthened by the MUI in Lampung society and how. This research uses a qualitative approach using data collection tools; interviews, observation and documentation, data obtained through primary data, namely: MUI management in Lampung Province, Ulama in Lampung Province, and Islamic religious figures and social observers in Lampung. The informant provided information related to the focus of this research. The validity of the data is used through technical triangulation, namely the integration of data obtained from interviews, observation and documentation with analysis steps through the stages of data reduction, data display and conclusion. Based on data findings in the field; The principles of Khairu Ummah which are strengthened in the Lampung community include; As-Shidqu, al-amanah wal-wafa bil 'ahdi, al 'is, at-ta'awun and istiqomah. The way to strengthen the principles of Khairu Ummah is by providing an example or qudwah hasanah for religious practice with the character of rahmatan lil'alamin with the Amar Ma'ruf Nahi Mungkar method and strengthening faith in Allah SWT. through ADW media, al-Ukhuwah Bulletin Publication, MUI on -lone, TV MUI and Mutiara Hikmah Ramadhan as well as the ta'lim assembly.